Utility of serial serum C-reactive protein in the diagnosis of neonatal infection - Sundarapandian, Santhakumar; Chinnakkannan, Selvakumar; Ahmed, M Shafath; Das, Rashmi Ranjan (Indian Journal of Child Health, 2017)
Introduction: C-reactive protein (CRP) has been used as a biomarker to diagnose neonatal sepsis. Aim: The aim of the study was to study the utility of serial CRP levels in the neonatal infection/sepsis diagnosis. Materials and Methods: Neonates admitted to a tertiary care teaching hospital were classified into three groups: proven sepsis (culture positive from any body fluid), probable sepsis (culture negative but clinical and laboratory parameters suggestive of sepsis), and no sepsis (not suggestive of sepsis). CRP was measured as follows: CRP 1 at the time of clinical presentation and CRP 2 and 3 at 24 and 48 h, respectively. Sensitivity, specificity, predictive values, and likelihood ratios were calculated. Results: Suspected infection/sepsis was evaluated as earlyonset (?72 h) in 300 neonates and late-onset (LONS) (>72 h) on 150 occasions in 100 neonates. There was a strong correlation etween the diagnoses of proven or probable sepsis and elevated CRP levels (?1.0 mg/dl), for both early- and LONS episodes, supporting the diagnostic utility of CRP. The sensitivity of CRP 2 was > CRP 1, but maximum sensitivity was achieved by CRP 3 level only. A CRP level has a much higher predictive value in ruling out than ruling in neonatal infection/sepsis (reaching almost 99-100% for both sepsis types). Conclusions: Serial CRP measurements are useful in the diagnosis of neonatal infection/sepsis. The predictive value of CRP 1 level being normal at initial evaluation cannot justify discontinuing antibiotic therapy. CRP 3 level may virtually rule out or rule in the diagnosis of neonatal sepsis.